Klippel-Trénaunay Syndrome with Intracranial Arteriovenous Malformation: A Rare Presentation - Mahniya F. Sadiq; Waqas Shuaib; Muhammad H. Tiwana; Jamlik-Omari Johnson; Faisal Khosa (Case Reports in Radiology)
Klippel-Trénaunay syndrome (KTS) is a rare vascular congenital anomaly affecting less than 200,000 people in the United States. Vascular malformations associated with KTS tend to affect slow flow systems: venous, capillary, and lymphatic systems. The nature of the syndrome leads to a higher risk for the development of arteriovenous malformations. Our case presentation describes a patient with KTS and an associated rare presentation of intraventricular arteriovenous malformation (AVM).